(untitled) (SAARC Journal of Agriculture, 2022)
Low profitability from jute farming, declining jute area and negligible pulse area are the rising concerns of farmers of Indo-Bangla subcontinent. This paper evaluated the extent of yield competition in jutemungbean intercropping with varying spatial geometry under alternate single row (SR) and double row (DR) planting. Two 2-year field experiments were conducted independently for the two systems of plantings involving jute (cv NJ 7010) and mungbean (cv TMB-37) arranged in systematic designs for 3×3×3 spacing and plant density combinations with three replications. Yield competition was assessed using indices. Intercropping was found productive and profitable compared to sole cropping. Land equivalent ratios (LER) and area × time equivalent ratios (ATER) always exceeded unity. Jute equivalent yield (JEY) increased in the range of 4.9-45.3% and 30.7-51.1% over sole jute fibre yield and mean monetary advantage index exceeded 27100 and 31800 ₹ ha-1 for SR and DR planting, respectively. Economic advantage was higher for spacing combinations of 40 cm (row to row) × 6.5-8 cm (jute to jute in a row) × 10-12 cm (mungbean to mungbean in a row) in SR planting and for DR system it was at a band-to-band spacing of 11 cm with plant densities of 40-50 m-2 for jute and 25-30 m-2 for mungbean. Dense and intimate planting of jute reduced mung seed yield due to light stress. DR planting seemed more advantageous. SAARC J. Agric., 19(2): 137-155 (2021)